INFORMATION TECHNOLOGIES IN THE FORMATION AND IMPLEMENTATION OF THE ENTERPRISE INNOVATION STRATEGY - DIACHKOV, Dmytro; SOBCHYSHYN, Vitaliy; VAKULENKO, Yuliia; USENKO, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article comprehensively investigates the role of information technologies (IT) in the formation and implementation of an enterprise’s innovation strategy under conditions of digital transformation and intensifying global competition. It is emphasized that IT today functions not only as a technical instrument for business support but as a strategic resource and a catalyst for innovation-driven growth. The authors explore the conceptual foundations of information technologies, analyzing various scientific definitions and highlighting their functional role in ensuring effective strategic management. The study identifies the innovative strategy as a key component of enterprise development, aimed at fostering technological renewal, flexibility, and sustainable competitiveness in a dynamic market environment. Special attention is paid to the integration of IT across all managerial levels – analytical, operational, and strategic – through the creation of a unified digital ecosystem. This ecosystem is based on advanced tools such as Big Data analytics, artificial intelligence, digital twins, and cloud computing, which together enhance data-driven decision-making, operational efficiency, and the capacity for innovation. The research also presents a systematization of business development strategies and justifies the innovative strategy as a fundamental mechanism for digital competitiveness. The authors conclude that comprehensive digitalization not only transforms business processes but also redefines management paradigms, promoting a culture of continuous learning, creativity, and openness to technological change. The results underline that the effective use of IT significantly increases innovation performance, reduces strategic risks, and ensures long-term sustainability. The paper’s theoretical and practical implications can serve as a methodological framework for developing integrated systems of digital innovation management in modern enterprises.